Preparation of Vegetable Waste-Derived Paper Incorporated with Activated Carbon for Delay Mango Ripening and its Application - Sriprom, Pongsert; Thongkham, Phaewa; Taweesukyingjaroen, Jurairat; Somphan, Apiruk; Manamoongmongkol, Kanjana; Assawaseangrat, Pornsawan (My University, 2026)
In this study, the vegetable waste-derived paper was developed from vegetable waste-derived fiber and Mahachanok mango seed-derived activated carbon to extend the shelf life of Golden Nam Dok Mai mangoes. Vegetable waste was subjected to alkaline processing using sodium hydroxide to extract plant-based fibers, which were then formed into paper sheets. Activated carbon, derived from Mahachanok mango seeds by carbonization at 450°C and activated by potassium permanganate (KMnO4), was incorporated into the vegetable waste-derived paper to enhance ethylene adsorption efficiency. Three formulations of ripening delay paper were prepared: paper without activated carbon, paper containing 10 g of activated carbon, and paper containing 20 g of activated carbon. The physical properties of the papers were evaluated in terms of tensile strength and water drop absorption. The vegetable waste-derived paper incorporated with 20 g activated carbon showed the highest performance among the developed papers (1.20 ± 0.24 MPa and 0.74 seconds, respectively). Application tests on Golden Nam Dok Mai mangoes showed that the 10 g activated carbon formulation was the most effective in preserving flesh color, maintaining firmness, and balancing total soluble solids (TSS) and titratable acidity (TA), indicating a delayed ripening process. Therefore, ripening delay paper synthesized from vegetable fiber and supplemented with 10 g of activated carbon per 1 kg of fruit was proven to effectively prolong mango shelf life by up to 3 days, demonstrating its potential as a biodegradable solution for postharvest quality preservation.
Keywords: activated carbon; delay ripening; mahachanok mango seed; vegetable waste; vegetable waste-derived paper